2015
DOI: 10.1007/s10826-015-0130-x
|View full text |Cite
|
Sign up to set email alerts
|

Coparenting in Stepfamilies: Maternal Promotion of Family Cohesiveness with Partner and with Father

Abstract: Coparenting refers to the support parents bring to each other when rearing a child. Supportive coparenting ensures cohesiveness of the family, which is linked with child outcomes. Little is known, however, about the co-parental relationship in stepfamilies between the custodial parent, usually the mother, and the new partner, and how it compares to coparenting with the father. This study addressed mother-reported coparenting in stepfamilies and also compared it with that in first-marriage families. Three dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 63 publications
(63 reference statements)
2
14
1
10
Order By: Relevance
“…With regard to the dimensions which affect the frequency of visits, besides fathers’ education, attachment confidence and marital status were found to increase the likelihood of fathers engaging in more frequent contacts with their children, while profiles of self‐perception did not. This finding is in line with literature showing that insecure attachment styles are associated with lower levels of parental involvement and that marital support is linked to higher parental engagement . Nevertheless, we found no relation between profiles of self‐perceive paternal role and frequency of contacts, despite existing findings supporting such a prediction in low‐risk conditions .…”
Section: Discussionsupporting
confidence: 92%
“…With regard to the dimensions which affect the frequency of visits, besides fathers’ education, attachment confidence and marital status were found to increase the likelihood of fathers engaging in more frequent contacts with their children, while profiles of self‐perception did not. This finding is in line with literature showing that insecure attachment styles are associated with lower levels of parental involvement and that marital support is linked to higher parental engagement . Nevertheless, we found no relation between profiles of self‐perceive paternal role and frequency of contacts, despite existing findings supporting such a prediction in low‐risk conditions .…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study, in the context of a community survey on social and psychological dimensions related to the functioning of stepfamilies, we investigated through questionnaires the presence of coparenting behaviors between mothers and their new partners compared with a control group of first-marriage families. Our results showed that behaviors such as conflict, promotion of family integrity, and disparagement are reported by mothers in the parent-stepparent relationship, although with reduced frequency than in first-marriage families (Favez, Widmer, Doan, & Tissot, 2015). This previous study (the main study) thus validated the relevance of considering coparenting in the mother-stepfather relationship.…”
supporting
confidence: 79%
“…Our results showed that behaviors such as conflict, promotion of family integrity, and disparagement are reported by mothers in the parent-stepparent relationship, although with reduced frequency than in first-marriage families (Favez, Widmer, Doan, & Tissot, 2015). In a previous study, in the context of a community survey on social and psychological dimensions related to the functioning of stepfamilies, we investigated through questionnaires the presence of coparenting behaviors between mothers and their new partners compared with a control group of first-marriage families.…”
mentioning
confidence: 63%
“…De plus, il existerait un lien de causalité entre la qualité de la relation coparentale entre parents et beaux-parents et la qualité de leur relation conjugale (Schrodt et Braithwaite, 2011). Enfin, d'après les mères, les interactions coparentales sont plus fréquentes entre mères et beaux-pères qu'entre mères et pères non hébergeants (Favez et al, 2015). En revanche, ces interactions coparentales, en particulier celles qui ont pour objectif la cohésion de la famille, sont moins élevées que dans les familles de première union.…”
Section: Coparentalité Avec Les Beaux-parents : Au Carrefour De Difféunclassified